Efektifitas Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan Dalam Meningkatkan Keamanan Dan Keselamatan Berlalu Lintas Di Kalangan Remaja - Chrisnanda Yovita Pricillia; Hermanto Silalahi; Diah Imaningrum S (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the effectiveness of Law Number 22 Year 2009 on Road Traffic and Transportation UULLAJ and the inhibiting factors for the implementation of Law Number 22 Year 2009 on Road Traffic and Transportation in improving traffic safety and security among teenagers in Pasuruan City. This research was conducted at the Traffic Unit (Satlantas) of Pasuruan City Police Station. The data obtained are primary data and secondary data through field research, source interviews and library research. The results of the study indicate that the rules contained in the UULLAJ are not effective in increasing security and safety, especially among adolescents, because there are still many violations committed by teenagers. Accidents can occur due to various factors, namely: lack of legal awareness of drivers, applying mobile phones when driving, not obeying traffic signs, not having a driving lisence, and reckless on the road, especially which are done by teenagers. As for the factors that inhibit the effectiveness of Law Number 22 Year 2009, namely: the use of vehicles by school children who still do not have a driving lisence (SIM), the parents also become obstacles by giving them vehicles to their children who do not have SIMs, community knowledge about Law Number 22 Year 2009 is still very minimal. Steps that can be taken so that our adolescents understand the importance of traffic awareness, are socialization that children who do not have a SIM must not bring motorized vehicles given their unstable psychological and mental conditions to deal with road events and lack of skill in running their vehicles.